Meso-Experimental Study on Tensile Characteristics of Clay - Yi Zhou; Meng Cui; Dequan Zhou; Xiaojia Wang; Xiao Fu (Advances in Civil Engineering)
This paper presents an experimental study on the meso-structure change of clay using an innovative testing system. It aims to evaluate the tensile characteristics of clay. The testing system designed in this paper includes a tensile loading device, an image acquisition device, and an image processing program, which can collect and process the meso-structural images of the soil sample and predict the location of tensile fracture zone with a small preloading. The tests were conducted with three different observation zones, including the tensile fracture zone (Zone 1), the adjacent area of tensile fracture zone (Zone 2), and the areas away from the tensile fracture zone (Zone 3). The results show that the development of cracks is continuous but not linear until tensile failure in Zone 1, and the cracks emerge but stop developing in Zone 2 with the penetration of the cracks in Zone 1, while there is only an overall deviation without any cracks in Zone 3. The variety of mesostructural quantitative parameters in Zone 1 can be divided into three stages: stable stage, rapid change stage, and failure stage. The changes of parameters in Zone 2 show a similar law with those in Zone 1, but the variation is smaller due to the cessation of cracks. The parameters in Zone 3 essentially remain unchanged throughout the whole procedure. According to the test results, the whole stretching process of clay can be divided into the sprouting, the development, and the penetration of cracks.